Rodinný dům - Pařízek, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Předmětem bakalářské práce je novostavba dvougeneračního rodinného domu v obci Březník. Objekt je osazen v mírně svažitém terénu na konci zástavby rodinných domů v okrajové části obce. Dům má jedno podzemní a dvě nadzemní podlaží. V prvním nadzemním podlaží je terasa, ze které je umožněn přístup na zahradu po samostatně stojícím ocelovém schodišti. Vedle rodinného domu je navržen dřevěný přístřešek s pultovou střechou pro dva osobní automobily. Nosné stěny v podzemním podlaží jsou provedeny ze ztraceného bednění Best a v nadzemních podlažích z cihelných tvárnic Porotherm. Střecha je sedlová s krytinou z ražených drážkových tašek Tondach.

The subject of this bachelor thesis is a new building of two-generation family house in the village of Březník. The building is situated in a slightly sloping terrain at the end of the construction of family houses on the outskirts of the village. The house has one underground and two above-ground floors. On the first floor there is i terrace from which acces to the garden is provided by a stand-alone steel staircase. Next to the family house is a wooden shed with a plank roof for two cars. The supporting walls in the underground floor are made of permanent formwork Best and in the above-ground floor of the Porotherm masonry elements. The roof is saddle with Tondach grooved tiles.
Detached house
Keywords: Rodinný dům; terasa; přístřešek; ocelové schodiště; sedlová střecha; ztracené bednění; Porotherm; Family house; terrace; shed; steel staircase; saddle roof; permanent formwork; Best; brick shapes; Porotherm